Prestasi Afektif Siswa Dilihat Dari Kedisiplinan Belajar Mereka - Putri Novianti; Dadan Nurulhaq; Saca Suhendi (UIN Sunan Gunung Djati Bandung, 2022)
The aims of this study to find out (1) the reality of the learning discipline at grade XI students of SMAN 1 Ciwidey, Bandung Barat district, (2) the reality of students’ affective (3) the correlation between both of them. This study used quantitative approach and correlation method located at grade XI students of SMAN 1 Ciwidey. The result of this study showed (1) the reality of the learning discipline at grade XI students of SMAN 1 Ciwidey was included in the high category, the data showed 4,33 (interval 3,40-4,19), (2) the reality of students’ affective is included in the positive category, the data showed 4,08 (interval 3,40 – 4,19), (3) the correlation between students’ learning discipline and their affective: (a) The correlation coefficient is included in the moderate category, the data showed 0,43 (interval 0,40-0,60), (b) the hypothesis is accepted, based on the calculation the data showed t-count (=3,92) > t-table (1,67). The result of the analysis of the level of the correlation effect obtained the result of 9% showing that there is an influence of student learning discipline with their affective achievement in the subjects of Religious Education and Character Class XI at SMAN 1 Ciwidey.